2013
DOI: 10.1016/j.socscimed.2013.05.036
|View full text |Cite
|
Sign up to set email alerts
|

What matters to older people with assisted living needs? A phenomenological analysis of the use and non-use of telehealth and telecare

Abstract: Telehealth and telecare research has been dominated by efficacy trials. The field lacks a sophisticated theorisation of [a] what matters to older people with assisted living needs; [b] how illness affects people's capacity to use technologies; and [c] the materiality of assistive technologies. We sought to develop a phenomenologically and socio-materially informed theoretical model of assistive technology use. Forty people aged 60-98 (recruited via NHS, social care and third sector) were visited at home severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
292
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(338 citation statements)
references
References 18 publications
12
292
0
10
Order By: Relevance
“…Previous scholarship has discussed these forms of mediation work in both gendered and generational terms (Greenhalgh et al 2013, Oudshoorn, 2012, Wyatt et al 2005) but here we found that these might cut across such distinctions. Thinking of a care infrastructure helps keep these contributions in view.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Previous scholarship has discussed these forms of mediation work in both gendered and generational terms (Greenhalgh et al 2013, Oudshoorn, 2012, Wyatt et al 2005) but here we found that these might cut across such distinctions. Thinking of a care infrastructure helps keep these contributions in view.…”
Section: Discussionmentioning
confidence: 47%
“…The emplacement of blood pressure monitors mediated their use (as in Hodgetts et al 2011) and non-use (see also Greenhalgh et al 2013). Apart from the networking capacities of devices, the more mundane fact that most monitors could run on batteries rather than mains electricity and were relatively small meant they were reasonably portable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, telehealth raises several challenges, including e-literacy, confidentiality and privacy, patient's data protection, and the medicalization of the living space, in addition to the symbolism that technology might endorse for some people or communities [12][13][14][15]. In the same vein, telehealth also raises issues related to digital democracy and the right of all citizens to equally benefit from advances made in digital health, which leads several authors to call for a better consideration of the perspectives of people and communities who are, or could be, affected by these issues [12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, telehealth also raises issues related to digital democracy and the right of all citizens to equally benefit from advances made in digital health, which leads several authors to call for a better consideration of the perspectives of people and communities who are, or could be, affected by these issues [12,[15][16][17][18][19]. In order to overcome such issues, at least in part, the idea of involving citizens-patients (the term refers to patients or their representatives, their family, as well as citizens, public and communities who are actual or potential users of health services) in the decisions concerning the development of telehealth services has been proposed [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%